Penjelasan Dokter dan Durasi Pengambilan Obat terhadap Loyalitas Pasien BPJS dengan Variabel Kepuasan Pasien sebagai Variabel Intervening - Ginting, Chrismis Novalinda; Agatha, Yuti Paramitha; Wau, Herbert (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of a doctor's explanation and duration of drug intake on BPJS patient loyalty, with patient satisfaction as an intervening variable. The research method used cross-sectional. The results showed that there was an effect of doctor's explanation on BPJS patient loyalty at RSU Royal Prima Medan P value <0.05, there was an effect of drug intake duration on BPJS patient loyalty at RSU Royal Prima Medan P value <0.05, there was an effect of doctor's explanation on patient satisfaction, there was an effect of drug intake duration on patient satisfaction, there was an effect of patient satisfaction mediating doctor's explanation on patient loyalty, there was an effect of patient satisfaction mediating drug intake duration on patient loyalty, and there was an effect of patient satisfaction on patient loyalty. This study concludes that the doctor's explanation and duration of drug intake affect patient loyalty. Keywords: Drug Taking Duration, Satisfaction, Loyalty, Doctor's Explanation